Agile Processes in Software Engineering and Extreme Programming: 17th International Conference, XP 2016, Edinburgh, UK, May 24-27, 2016, Proceedings (Springer Nature, 2021)
Business Information Systems; Software Engineering; Software Management; Management of Computing and Information Systems